Cross-cultural management in work organisations / Raymond French - French, Ray
This volume provides an evaluation of frameworks for understanding cross-cultural differences as they affect workplace behaviour and the management of people. It also examines the inter-cultural competencies needed by managers dealing with employees from different cultural backgrounds.